Epidemiology of Chronic Kidney Diseases (CKD) in Malaysia and Pakistan, Pathophysiology of CKD-Associated Pruritus and Other CKD-Associated Dermatological Disorders - Inayat Ur Rehman; Tahir Mehmood Khan (Progress in Microbes and Molecular Biology)
Almost 50–90% of chronic kidney disease patients undergoing haemodialysis have been reported to have Chronic kidney disease-associated pruritus (CKD-aP). The intensity of CKD-aP may vary from a mild itch to an unbearable pruritic sensation which interferes with the patient’s quality of life. CKD-aP has become one of the upmost distressing cutaneous and most common symptom of chronic kidney disease which is often overlooked by nephrologists, primary care physicians, and other health-care professionals. Typically sleep disorders, mental and social well-being have been correlated with chronic kidney disease patients. With that this article presents vital comprehensive review which includes epidemiology of chronic kidney disease in Malaysia and Pakistan, CKD-associated pruritus and other dermatological disorders associated with chronic kidney diseases, pathophysiology of CKD-associated pruritus, clinical features of chronic kidney disease-associated pruritus, diagnosis of CKD-associated uremic pruritus, differential diagnosis of CKD-associated uremic pruritus, assessment and quantification of pruritus severity.